2018
DOI: 10.1002/mp.12781
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐vinyl acetate foam as a new lung substitute in radiotherapy

Abstract: The EVA40 is an excellent cork-like lung substitute for radiotherapy applications. From a sole material used in footwear, it is possible to obtain a lung substitute that mimics the physical and dosimetric characteristics of ICRU lung tissue even better than the RANDO commercial phantom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previous research by Marques and Mancha reported the use of PEVA 40% as a foam sheet due to ease of manufacture and design in producing a novel lung replacement in radiotherapy. This copolymer can effectively mimic the dosimetric and physical features of ICRU lung tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Marques and Mancha reported the use of PEVA 40% as a foam sheet due to ease of manufacture and design in producing a novel lung replacement in radiotherapy. This copolymer can effectively mimic the dosimetric and physical features of ICRU lung tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that foams and other urethane‐based materials can closely model lung tissue . However, these lung phantoms were designed to work in CT imaging or radiotherapy dosimetry applications and did not require embedded radioactivity nor the corresponding short construction time needed in SPECT phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that foams and other urethane-based materials can closely model lung tissue. [3][4][5][6] However, these lung phantoms were designed to work in CT imaging or radiotherapy dosimetry applications and did not require embedded radioactivity nor the corresponding short construction time needed in SPECT phantoms. The purpose of this work was to create a new lung phantom using expanding polyurethane foam (EPF) that more closely models the density of actual lung tissue and exhibits a more uniform activity distribution than the polystyrene and water-based method.…”
Section: Introductionmentioning
confidence: 99%